2017
DOI: 10.18632/oncotarget.19260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of earlier-proteinuria on graft functions after one-year living donor renal transplantation

Abstract: BackgroundProteinuria is an indicator of subsequent renal function decline in most nephropathies and early proteinuria has been assumed to be a risk factor of poor kidney transplant outcomes. However, there is no information about the effect of earlier-proteinuria at the first week on short-term graft function after living donor renal transplantation.MethodsRetrospective cohort study of 439 living donor kidney transplants to analyze the effect of early proteinuria at 7-day post-transplantation on short-term pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The severity of proteinuria after KT has been shown to be inversely associated with graft survival and favorable patient outcomes [2][3][4][13][14][15][16][17][18][19]. Similarly, a recent large cohort study demonstrated that the severity of proteinuria at 3 months, 1 year, 2 years, and 6 years after KT, as well as at the time of allograft biopsy, was inversely associated with graft survival [16].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The severity of proteinuria after KT has been shown to be inversely associated with graft survival and favorable patient outcomes [2][3][4][13][14][15][16][17][18][19]. Similarly, a recent large cohort study demonstrated that the severity of proteinuria at 3 months, 1 year, 2 years, and 6 years after KT, as well as at the time of allograft biopsy, was inversely associated with graft survival [16].…”
Section: Discussionmentioning
confidence: 95%
“…However, there were conflicting results regarding the prognostic value of proteinuria at 1 month after KT [4,14]. A few studies have evaluated the clinical value of proteinuria less than 1 month after transplant, and one among them showed an association between proteinuria measured 1 week posttransplant and graft function [15]; however, this study included only LDKT recipients, and proteinuria was assessed using 24-hour urine collection within 1 week posttransplant, but only by qualitative tests were used after 1 month [15]. Our study investigated the clinical value of quantitative measurement of urine protein excretion at different time points, including during the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 99%